Impacto do investimento na área administrativa e fiscal: caso do Programa Nacional de Apoio a Modernização Administrativa e Fiscal nos Munícipios Brasileiros - PNAFM no Município de Fortaleza - Ferreira, André Ramos (2020)
In order to improve management and efficiency in the administrative and tax areas, the city of Fortaleza, capital of the State of Ceará, adhered to the National Support Program for Administrative and Tax Management in Brazilian Municipalities - PNAFM during 2004 and 2018. The primary objective of the program is to increase revenue and reduce expenditure in order to improve the autonomy of municipalities in terms of self-sufficiency. Fortaleza - CE was the only municipality in the period to have 3 (three) completed projects under the program and this work aims to verify the effects of PNAFM on tax revenue (IPTU, ISS and ITBI) in the city of Fortaleza. Given the difficulties of using usual econometric techniques for policy evaluation, an analysis of the dynamics and structural break test of the taxes targeted by the program is used, together with a comparison of these same taxes from a capital with social aspects similar to Fortaleza. The results indicate that the PNAFM has no direct effect on the collection of these taxes in Fortaleza.